High Resolution Experimental and Computational Methods for Modelling Multiple Row Effusion Cooling Performance - Murray, A; Ireland, P; Wong, T; Tang, S; Rawlinson, A (European Turbomachinery Society, 2017)
The continuing rise in turbine entry temperatures has necessitated the development of evermore advanced cooling techniques. Effusion cooling, which is characterised by a high density of film holes operating at low blowing ratios, represents one possible mechanism for achieving high overall cooling effectiveness. This paper presents an experimental investigation performed on flat-plate, effusion-type cooling geometries (with primary hole pitches of 3.0D and 5.75D) using pressure sensitive paint to yield high-resolution film effectiveness distributions using the heat/mass transfer analogy. CFD was used to model the setup computationally, with results comparing favourably to the experiments. The CFD domain was then altered to model a single hole. A superposition method was developed and applied to the two dimensional film effectiveness distribution, yielding data for an array of closely-packed holes. The method produced satisfactory results at higher pitches, but at lower pitches, high levels of jet interactions reduced the performance of the superposition method.